2021
DOI: 10.1371/journal.pone.0247639
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of clients on preventive measures of COVID-19 pandemic among governmental health facilities in South Wollo, Ethiopia: A facility-based cross-sectional study

Abstract: Introduction Coronavirus-19 is a global health challenge and need an immediate action. Thus, understanding client’s knowledge about SARS-COV2 causes, roots of transmissions, and prevention strategies are urgently warranted. Although there were global studies reported knowledge and preventive practices of COVID-19, but the information is not representative and inclusive for Ethiopia. Thus, the current study is done to identify the knowledge and the prevention strategies for COVID-19 among clients in South Wollo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…The great majority (378, 90.6%) of participants knew that proper hand washing procedures (for at least 20 seconds with soap and water) can prevent COVID-19, a result similar to findings in studies in southwestern Ethiopia (92.7%), 27 South Wollo, Ethiopia (93.83%), 28 in Bangladesh (93.5%), 29 Egypt (94%), 30 and Nepal (97%), 31 but higher than in Addis Zemen Hospital, (78.5%), 32 Gondar City (53%) 33 and Amhara Region (79%, 34 all in Ethiopia. These discrepancies may be due to differences in the socio-demographic characteristics of the study populations and the effectiveness of national and local COVID-19 prevention programs.…”
Section: Discussionsupporting
confidence: 74%
“…The great majority (378, 90.6%) of participants knew that proper hand washing procedures (for at least 20 seconds with soap and water) can prevent COVID-19, a result similar to findings in studies in southwestern Ethiopia (92.7%), 27 South Wollo, Ethiopia (93.83%), 28 in Bangladesh (93.5%), 29 Egypt (94%), 30 and Nepal (97%), 31 but higher than in Addis Zemen Hospital, (78.5%), 32 Gondar City (53%) 33 and Amhara Region (79%, 34 all in Ethiopia. These discrepancies may be due to differences in the socio-demographic characteristics of the study populations and the effectiveness of national and local COVID-19 prevention programs.…”
Section: Discussionsupporting
confidence: 74%
“…Previous literature regarding prevention practices and awareness regarding COVID-19 on the global platform have focused on topics such as perspectives, awareness levels and barriers reported by health professionals in implementing prevention strategies,25–28 42 and the attitudes, knowledge levels and practices followed among certain populations 25 29–34 43. Literature focused on the Indian population en masse highlights the need for knowledge and awareness programmes regarding COVID-19,20–24 44 and prevention practices currently being followed 20 21 23.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable literature has been published regarding the knowledge and awareness of COVID-19 and prevention practices across populations,20–34 highlighting the need for the same. However, among the nomadic truck driver population, knowledge, awareness and prevention practice, assessments have been limited to other health conditions 35–39.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds, such as -glucans, were found in these L. rhinocerus MB-EPS extracts; use of glucans have gained appeal in recent years for a number of emerging applications including biopolymers 30 and biomedicines 31 . It is notable that mushroom-derived -glucans have many new therapeutic properties, including (a) potential new or complementary immunotherapies against Coronavirus disease (SARS-CoV-2) 14 , (b) potential new therapeutic agent for mitigating diseases associated with gastrointestinal mucosal damage, such as peptic ulcers and inflammatory bowel disease 32 , (c) potential as anticancer drugs for lung and breast cancer 33 , and (d) potentially asthmatic treatment 23,34 . However, there is a marked gap in knowledge surrounding the toxicity (if any), of these mushroom-derived bioactive compounds; particularly use of Zebrafish trials that would aid product development and implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported on the efficacy of EPS from medicinal mushrooms to ameliorate pro-and anti-inflammatory responses using ex vivo and in vivo infection models with therapeutic potential 12,14,22 . Aqueous extracts of L. rhinocerotis were reported to help reduce asthmarelated variables in asthma model 23 . In addition, a previous toxicity study indicated that feeding 1000 mg/kg of L. rhinocerus extract to rats had no detrimental consequences, hence considered safe 24 .…”
Section: Introductionmentioning
confidence: 99%